2008
DOI: 10.2131/jts.33.386
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letter to the Editor

Abstract: We have serious concerns about the above paper, given the sensitivity of the issue of the potential risks from nan otubes. The paper claims to demonstrate that nanotubes have the potential to cause mesothelioma but we take issue with this in three main aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…These studies find that CNTs aggregate together, generally in the liver, spleen and lung tissue. It has been suggested that CNT aggregates have similar carcinogenic properties to asbestos fibers [196][197][198]. Many factors modulate the aggregation and the effective clearance of CNTs.…”
Section: Future Directionsmentioning
confidence: 99%
“…These studies find that CNTs aggregate together, generally in the liver, spleen and lung tissue. It has been suggested that CNT aggregates have similar carcinogenic properties to asbestos fibers [196][197][198]. Many factors modulate the aggregation and the effective clearance of CNTs.…”
Section: Future Directionsmentioning
confidence: 99%
“…9 Because CNTs have a ber-like shape, similar to that of asbestos, there is increasing public concern that respiratory exposure to CNTs might increase the risk of lung cancer. [10][11][12] Moreover, the stable graphite structure of CNTs makes them resistant to biodegradation, increasing concerns about their long-term safety. According to the International Agency for Research on Cancer (IARC, 2002), lung brosis and thoracic tumors are oen observed when ber clearance from the lungs is slow.…”
Section: Introductionmentioning
confidence: 99%
“…Certain types of CNTs might induce mesothelioma-like lesions in mice, in a manner similar to that observed for mesothelioma induced by asbestos. 460,461,[462][463][464] Following peritoneal injection, long and multiwalled CNTs produce inflammation and fibrosis in the peritoneal cavity similarly to asbestos fibers whereas short tangled ones did not cause any significant inflammation. 461,465 Diameter and rigidity of multiwalled CNTs are critical factors in mesothelial injury and carcinogenesis.…”
Section: Nanomedicines Based On Hybrid Biomimetic Systemsmentioning
confidence: 99%